2021
DOI: 10.3389/fphys.2020.612188
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cardiac Circadian Rhythm Deconditioning Induced by 5-to-60 Days of Head-Down Bed Rest

Abstract: Head-down tilt (HDT) bed rest elicits changes in cardiac circadian rhythms, generating possible adverse health outcomes such as increased arrhythmic risk. Our aim was to study the impact of HDT duration on the circadian rhythms of heart beat (RR) and ventricular repolarization (QTend) duration intervals from 24-h Holter ECG recordings acquired in 63 subjects during six different HDT bed rest campaigns of different duration (two 5-day, two 21-day, and two 60-day). Circadian rhythms of RR and QTend intervals ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Day-night rhythms of HR and BP were visibly preserved, however, the night dip in HR and BP was slightly flattened. Flattening of day-night oscillations for HR is in agreement with findings on 5-, 21-, and 60-day HDBR, revealing such flattening progressing with the duration of bedrest 62 . In line with the early lower limb musculoskeletal deconditioning mentioned above, continuous 24 h recording of physical activity and HR demonstrates a sedentarily-like lifestyle especially pronounced on the legs.…”
Section: Discussionsupporting
confidence: 89%
“…Day-night rhythms of HR and BP were visibly preserved, however, the night dip in HR and BP was slightly flattened. Flattening of day-night oscillations for HR is in agreement with findings on 5-, 21-, and 60-day HDBR, revealing such flattening progressing with the duration of bedrest 62 . In line with the early lower limb musculoskeletal deconditioning mentioned above, continuous 24 h recording of physical activity and HR demonstrates a sedentarily-like lifestyle especially pronounced on the legs.…”
Section: Discussionsupporting
confidence: 89%
“…Of note, for technical reasons, we were limited to continuous recordings of 21 h. We did not perform specific circadian analysis. However, a recent study specifically evaluating circadian rhythms of R-R intervals in 5-, 21-, and 60-day HDBR using Cosinor analysis ( Solbiati et al, 2021 ) revealed flattening of day–night oscillations for R-R intervals progressing with the duration of bedrest. These results are in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to exploring the relationship between circadian disruptions and sleep in future studies, it will also be important to identify the effects of circadian changes on behavior and cognition. Several studies have shown adverse effects of bed rest on brain function and cognitive performance ( Lipnicki and Gunga, 2009 ; Brauns et al, 2019 ; Friedl-Werner et al, 2020 ; Basner et al, 2021 ), mental health ( Liu et al, 2012 ; Stavrou et al, 2018 ), cardio-vascular changes ( Solbiati et al, 2021 ), and metabolic regulation ( Dandanell et al, 2016 ; Dirks et al, 2016 ) that can be associated with a lack of sleep ( Mullington et al, 2009 ; Anderson and Bradley, 2013 ; Goel et al, 2013 ). To mitigate the adverse neurophysiological and psychological effects associated with circadian disruptions, effective countermeasures are needed to maintain the entrainment of central and peripheral clocks.…”
Section: Discussionmentioning
confidence: 99%